The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1677/joe.0.1660205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unilateral or bilateral superior ovarian nerve section in infantile rats on follicular growth

Abstract: We report the effects that sectioning the superior ovarian nerve of infantile female rats has on their follicular development at different ages before puberty. Compared with the control group, sham-operated animals showed a significant decrease in the number of measured follicles in right and left ovaries, although no difference in the follicular atresia ratio was observed. Animals with a sectioned left superior ovarian nerve (SON), killed 12 days after surgery had a significant increase in the number of folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In the present experiment, the most pronounced decrease in the secretion of E 1 , E 2 and LH was observed in gilts with denervated ovaries during the perioestrous period. A similar phenomenon was reported earlier in rats (Lara et al, 1990b;Moran et al, 2000) as well as in gilts (Jana et al, 2005). A lack of the preovulatory LH surge in the gilts after neurectomy, found in our study, was probably caused by a decrease in oestrogen concentration during the perioestrous period, leading to a disturbance in positive and negative feedback of LH secretion.…”
Section: Discussionsupporting
confidence: 89%
“…In the present experiment, the most pronounced decrease in the secretion of E 1 , E 2 and LH was observed in gilts with denervated ovaries during the perioestrous period. A similar phenomenon was reported earlier in rats (Lara et al, 1990b;Moran et al, 2000) as well as in gilts (Jana et al, 2005). A lack of the preovulatory LH surge in the gilts after neurectomy, found in our study, was probably caused by a decrease in oestrogen concentration during the perioestrous period, leading to a disturbance in positive and negative feedback of LH secretion.…”
Section: Discussionsupporting
confidence: 89%
“…The degree of participation of the SON in the ovarian compensatory hypertrophy depends on the estrus cycle stage in which the ovariectomy and SON transection are performed (Chá vez and Dominguez, 1994). Participation of the SON has also been reported in the exogenous gonadotropin administration effect in juvenile animals, and a different estradiol and progesterone level has been observed at distinct times after SON transection (Morales et al, 1998;Moran et al, 2000).…”
Section: Innervation and Ovarian Functionmentioning
confidence: 90%
“…A similar effect is found in rats, where a bilateral denervation of the SON decreases the serum level of oestradiol, progesterone and the number of developing follicles. In addition, when a unilateral denervation of the SON was assessed, a decrease in the number of follicles was observed in the denervated ovary and a compensation (observed as an increase in the number of follicles) was observed in the innervated ovary (Moran et al 2000). In addition, it has been demonstrated that the sympathetic innervation of follicles influences follicular maturation/growth (Mayerhofer et al 1997, Paredes et al 2011, steroidal secretion (Hernandez et al 1988, Barria et al 1993 and ovulation (Kannisto et al 1985).…”
Section: Sympathetic Innervation and Ovarian Ageingmentioning
confidence: 99%
“…This means that the sympathetic adrenergic vasoconstrictor response in the ovary is well preserved in rats aged 28-31 months old. In addition to regulating ovarian blood flow, extrinsic ovarian innervation directly regulates steroidogenesis (Aguado & Ojeda 1984) and follicular development (Lara et al 1993, Moran et al 2000, Rosa et al 2003, Doganay et al 2010, Zhang et al 2010. Both α and β adrenergic receptors are expressed in the ovarian follicles (Aguado et al 1982, Barria et al 1993, Itoh & Ishizuka 2005, Fernandois et al 2012, and direct effects of NE on follicles could be produced by α1 and β2 adrenergic receptor stimulation (Laszlovszky & Erdo 1983, Itoh & Ishizuka 2005.…”
Section: Sympathetic Innervation and Ovarian Ageingmentioning
confidence: 99%